Initiating Smart Grid Techniques for Efficient Energy Management - Barra, Ling; Xavier, Embrechts; Margarida, Kruger (Journal of Moeslim Research Technik, 2024)
In this modern era, the demand for energy continues to increase along with population growth and technological development. Conventional energy distribution systems are increasingly unable to address the challenges of efficiency, reliability and sustainability. Therefore, the Smart Grid concept emerges as an innovative solution to improve energy management efficiently. This research aims to initiate Smart Grid techniques that can improve efficiency in energy management, reduce wastage, and ensure stable and reliable energy distribution. The research methods used include an in-depth literature study on Smart Grid technology, data analysis from Smart Grid implementations in various countries, and simulation and modeling to test the effectiveness of the proposed techniques in the local context. The results show that the implementation of Smart Grid can increase the efficiency of energy management by up to 30%. In addition, the proposed Smart Grid techniques are able to better integrate renewable energy sources, reduce peak loads, and improve response to grid disturbances. This research concludes that Smart Grid techniques have great potential to revolutionize energy management. With proper implementation, Smart Grid can be an effective solution to future energy challenges, ensuring more efficient, reliable and sustainable energy distribution.